Ethno-conservation of New Guinea Singing Dog among Tribes in Pegunungan Tengah, Papua, Indonesia - Syawal, Arni; Pudyatmoko, Satyawan; Faida, Lies Rahayu Wijayanti; Sirami, Elieser Viktor; Setyadi, Esti Gesang; Puradyatmika, Pratita; Suwandi, Rendy Enggar; Imron, Muhammad Ali (Forest and Society, 2023)
Interactions between humans and carnivores have been range from positive to negative, occasionally leading to human-wildlife conflict in many parts of the world. While dogs have roles to support humans, wild dogs such as wolf, dingoes, and singing dogs have both potential positive and negative roles for humans. We gathered knowledge among tribes in Pegunungan Tengah of Papua, Indonesia on their interactions with the New Guinea Singing Dog (NGSD) using an ethno-conservation approach. We conducted in-depth interviews using both emit and etic approaches with informants from the Amungme, Damal, Moni and Dani (Lani) tribes, who live in the habitat of the dog. Data were analyzed using phenomenological, content analysis, and analytical induction processes. The four tribes have traditional knowledge about the dog and its habitat, thus forming behavioral patterns, belief systems and cultural values toward NGSD. The ethno-conservation of these tribes is reflected in their culture as results from their ability to identify the dog’s sensitivity to the change of environment including human disturbances, water quality and food availability. The tribes also limit themselves to share information about NGSD to outsiders and respect the dogs as their ancestors. Residents of the four Indigenous tribes of Pegunungan Tengah believe that NGSD is the reincarnation and avatar of the dwelling spirits of their ancestors. We discuss the implications of these findings for the conservation of this non-protected species by the Indonesian government, but endemic to Papua.